Sala de cinema: da comunicação à experiência - Barra, Douglas Renê (Universidade do Vale do Rio dos Sinos, 2011)
The research focuses on analyzing the strategic design and the cinema in seeking to understand the consumer experience in the Brazilian cinematographic productions. Once settled, the issue of this study: How the possible experiences of relationship between the viewer and the cinematographic productions occur? How to qualify the experience of the cinema consumption? For data collection, the multiple case study was used, cinematographic productions (one national and one international) and their dissemination strategies, were also conducted interviews with viewers of a brazilian production currently in theaters and interviews with professional experts in the audiovisual market. Afterwards, data were analyzed by content analysis. One of the findings was that the consumer experiences in cinema do not become memorable, or extraordinary, when the movie is shown in isolation to communication strategies and services.
Keywords: Design estratégico; Experiência; Consumo cinematográfico; Strategic design; Experience; Cinema consumption; ACCNPQ::Ciências Sociais Aplicadas::Desenho Industrial